2022
DOI: 10.1097/md.0000000000028496
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and electroacupuncture for stroke

Abstract: Background: The aim of this study was to undertake a systematic overview of meta-analyses and published systematic reviews to identify whether and when acupunctureand electroacupuncture are deemed efficacious treatment options for stroke and stroke-related disorders. Methods: Four databases, namely, PubMed, AMED, EMBASE, and the Cochrane Library will be searched from their inception. Two reviewers will independently perform study selection, data extraction, and assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Acupuncture involves inserting thin needles into specific body points to stimulate natural healing and well-being ( 8 ). Electro-acupuncture (EA) adds small electrical currents to acupoints to enhance effects ( 9 ). Although clinical and experimental studies suggest that EA relieves knee pain ( 5 , 10 , 11 ), its efficacy for OA requires more research.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture involves inserting thin needles into specific body points to stimulate natural healing and well-being ( 8 ). Electro-acupuncture (EA) adds small electrical currents to acupoints to enhance effects ( 9 ). Although clinical and experimental studies suggest that EA relieves knee pain ( 5 , 10 , 11 ), its efficacy for OA requires more research.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that it may help improve motor function and physical performance in conditions of stroke. 35 It’s important to note that the clinical effects of electroacupuncture can vary depending on the specific condition being treated, individual patient factors, and the expertise of the practitioner.
Figure 1 Electroacupuncture treatment site.
…”
Section: Introductionmentioning
confidence: 99%